Biomechanical and biological limits in artistic gymnastics - Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Artistic gymnastics increased excessively the difficulty of single elements and entire routines in the last decades. Biomechanical and biological factors related the performance enhancement indicate that the potential of the musculo-skeletal System seems to be close to the limits while the neural motor control Systems have already achieved the ultimate tolerance limits. Strategies to ensure that the neural Systems' stress stays below the critical limits are not well understood. A further increase of difficulty in the particular sport will increase the risk of failure of the biomechanical and biological Systems. Acute and chronic severe tissue injuries are reported from male and female artistic gymnastics. In general mechanical loading of the musculoskeletal System is a prerequisite for morphological and functional adaptation of biological material. But there are indicators that stress and strain in artistic gymnastics increase to a level which exceed the mechanical limits of the individual structures. Artistic gymnastics seem to be close to the biomechanical and biological limits. A further increase of the difficulty in this sport and an increase of mechanical energy applied to the Systems may lead to more frequent failures in both the biomechanical and the biological components.